Whatever happened to Uncle Albert? and other puzzling plays - Alexander, Sue; Huffman, Tom (New York Houghton Mifflin/Clarion Books, 1980)
Five short plays for young people featuring humor and suspense.
Keywords: Children's plays, American; Detective and mystery plays, American